Validation of the Applied Biosystems 7500 Fast Instrument for the Detection of Salmonellae with SureTect Salmonella Species PCR Kit. (27th November 2019) - Cloke, Jonathan; Evans, Katharine; Crabtree, David; Hughes, Annette; Simpson, Helen
Abstract: The Thermo Scientific SureTect™ Salmonella species real-time PCR assay is a rapid alternative method designed for the detection of salmonellae in a wide range of foods, animal feeds, and production-environment samples. The assay has previously been validated according to the AOAC Research Institute Performance Tested Methods SM program using Thermo Scientific PikoReal™ PCR cycler and Thermo Scientific SureTect Software Performance Tested Method 051303). This report details the method-modification study performed to validate an updated assay format, utilizing a reduced target probe concentration and an extension of the PCR cycler platform to enable the use of the kit with a Applied Biosystems 7500 Fast PCR cycler and Applied Biosystems RapidFinder™ Express 2.0 software. During this validation study, a matrix study was conducted on a subset of the method's claimed matrixes, comparing the performance of the modified SureTect Salmonella species kit (a reduced target probe concentration with a 7500 Fast platform) to the reference method detailed in ISO 6579:2002. No significant difference by probability of detection statistical analysis was found between SureTect or International Organization for Standardization methods for any of the matrixes analyzed during the study. Inclusivity and exclusivity studies using the modified method demonstrated accurate results for the 117 Salmonella and 36 non- Salmonella strains tested. Multiple production lots of the newly formatted kit were evaluated and found to be consistent with the current assay. Robustness studies confirmed that the change to the kit had no impact on the assay's performance when alterations were made to method parameters having the greatest potential impact on assay performance.